The Effect of Mupirocin- and Fusidic Acid-nasal Packings, Placed after Septoplasty, on the Nasal Bacterial Profile. Issue 4 (October 2016) - Bilici, Suat; Durna, Yusuf Muhammed; Yigit, Ozgur; Karatas, Aysel; Cimen, Cansu; Fincanci, Muzaffer; Gökduman, Ali Riza
Aim: To examine the effects, after septoplasty, of local antibiotic pomades as an alternative to prophylactic antibiotic use, which is a controversial matter among the otolaryngologists, on nasal flora and bacterial growth. Material and Method: Nasal packings placed after septoplasty surgery to provide septal stabilization and bleeding control pose a risk in terms of infection. In this study, 106 patients, who were examined by comparing mupirocin- and fusidic acid-soaked packings and antibiotic-free packings, were divided into three groups. Nasal cultures were obtained from each patient twice, before the surgery and on the second day immediately after the packings were removed, and the culture results were statistically compared. Results: In the mupirocin group (group 2), postoperative normal flora growth rate was significantly higher than in the fusidic acid group (group 3) and the antibiotic-free group (group 1) (p < 0.024). In the mupirocin group (group 2), the gram-positive growth rate in the postoperative period showed a significant decrease when compared when the preoperative period (p < 0.05) (5.7%). In the fusidic acid group (group 3), the postoperative gram-positive rate showed a significant decrease compared with the preoperative period (p < 0.05). In group 2, the postoperative methicillin-resistant Staphylococcus aureus rate showed a significant decrease than in the preoperative period (2.9%) (p < 0.05). Similarly, in group 3, the postoperative methicillin-resistant S. aureus rate showed a significant decrease compared with that of the preoperative period (11.1%) (p < 0.05). Conclusion: Use of mupirocin- and fusidic acid-soaked nasal packings after septoplasty significantly decreased, especially, postoperative gram-positive bacterial growth in nasal cultures. Although systemic antibiotherapy was not administered, the lack of local and systemic infection findings was an important result that we obtained in terms of clinical use. Usage advantages of mupirocin and fusidic acid soaked packings are an easily applicable, cost-effective, and safe method.